Research Technology of Stevia - Rashid, Zahida; Ahngar, Tanveer Ahmad; Nazir, Aijaz; Dar, Z. A.; Khuroo, N. S.; Majeed, Shabina; Naseer, Sabeena; Bashir, Sabiya; Rakshanda, A.; Iqbal, Sadaf; Jan, Seerat (Cutting-edge Research in Agricultural Sciences Vol. 6, 2021)
Nature has bestowed us with great reservoir of sustainable resources beneficial for mankind. Whatever be the state of resources, it has been seen that nature has provided all these resources as an answer to this world’s concerns. Out of all these resources, researchers have only been able to explore a handful as is evident by the fact that there are nearly 2.5 million plants and herbs existing on earth, out of which only one per cent has been acknowledged through scientific studies to have real therapeutic value when used in extract form by humans. Virtually all such plants have been discovered and put to wide spread use in traditional medical systems through information derived from their use in folk medicine, ethno medicine or traditional medicine. Stevia rebaudiana Bertoni is a herb that has been used for centuries by the Guarani Indians of Paraguay both as a sweetener and as a medicine. Stevia has been introduced as a crop in a number of countries including China, Japan, Brazil, Korea, Mexico, United States, Canada, India and Indonesia. In India it was first introduced in Banglore by Banglore based Madhuram Agro. Currently stevia production is centred in China and the major market is in Japan. The largest user is Japan which began cultivating stevia in hot houses in 1954 providing the researchers a ray of hope that stevia could be grown in temperate climate also. Research carried out at Institute of Himalayan Bio-resource Technology (IHBT), Palampur has shown its production potential as an intercrop and have extensively reported its various properties for commercial cultivation paving a ray of hope for getting its potential yield under the temperate conditions of Kashmir Valley.